Algeria : Report on the Observance of Standards and Codes-Fiscal Transparency Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Algeria's report on the Observance of Standards and Codes reviews the Fiscal Transparency Module. The Bank of Algeria (BA) does not apply multicurrency practices and does not require import deposits and there are, therefore, no quasi-fiscal activities in exchange regime-related operations. As for financial system-related operations, no bailouts have been carried out by the BA and there are no longer any caps on credit. Privatization procedures are characterized by considerable flexibility, which in practice limits transparency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet